2016
DOI: 10.1073/pnas.1602079113
|View full text |Cite
|
Sign up to set email alerts
|

HIFI-α activation underlies a functional switch in the paradoxical role of Ezh2/PRC2 in breast cancer

Abstract: Despite the established oncogenic function of Polycomb repressive complex 2 (PRC2) in human cancers, its role as a tumor suppressor is also evident; however, the mechanism underlying the regulation of the paradoxical functions of PRC2 in tumorigenesis is poorly understood. Here we show that hypoxia-inducible factor 1, α-subunit (HIFI-α) is a crucial modulator of PRC2 and enhancer of zeste 2 (EZH2) function in breast cancer. Interrogating the genomic expression of breast cancer indicates high HIF1A activity cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 68 publications
3
63
1
Order By: Relevance
“…Chang et al (33) reported that in breast tumor initiating cells (BTICs), the transactivation function mediated by Hif-1α significantly upregulates EZH2 expression, whereas high EZH2 expression causes BTIC proliferation and promotes their progression. The conserved HRE sequence that interacts with Hif-1α was identified in the promoter region of EZH2, which confirmed that hypoxia induces Hif-1α to bind to this HRE region to activate EZH2 transcription, and to promote breast cancer growth (34). DZNep was the first discovered inhibitor of the enzyme activity of EZH2.…”
Section: Discussionmentioning
confidence: 64%
“…Chang et al (33) reported that in breast tumor initiating cells (BTICs), the transactivation function mediated by Hif-1α significantly upregulates EZH2 expression, whereas high EZH2 expression causes BTIC proliferation and promotes their progression. The conserved HRE sequence that interacts with Hif-1α was identified in the promoter region of EZH2, which confirmed that hypoxia induces Hif-1α to bind to this HRE region to activate EZH2 transcription, and to promote breast cancer growth (34). DZNep was the first discovered inhibitor of the enzyme activity of EZH2.…”
Section: Discussionmentioning
confidence: 64%
“…The present study also demonstrates major roles for both HIF1␣ and TWIST1 in TNBC tumor maintenance/growth (HIF1␣) and metastasis (TWIST1). To date, the literature on the role of TWIST1 and HIF1␣ in TNBC has been limited, with HIF1␣ even playing a paradoxical role as a modifier of the tumor suppressing function of PRC2 (17)(18)(19). In this study, a major role was identified for TWIST1 in both the AnR and downstream metastasis of TNBC, as down-regulation of this DNA trans-factor led to significant loss of AnR and, subsequently, a reduction in the metastatic rate enhanced by CPEB2B expression.…”
Section: Cpeb2 Rna Splicing Regulates Emt and Hypoxic Responsesmentioning
confidence: 73%
“…Enhancer of zeste homologue 2 (EZH2), as a histone methyltransferase, is a catalytic subunit of polycomb repressive complex 2 (PRC2) which induces transcriptional inhibition through the tri-methylation of lysine residue 27 on histone H3 (H3K27m3) (6). Abnormal activities of DNA methyltransferases lead to epigenetic changes of many genes that contribute to carcinogenesis (7).…”
Section: Introductionmentioning
confidence: 99%